Capacitive resistivity method and reclassification of geoelectric methods for hydrogeological and underground contamination studies - Aquino, Wagner [UNESP]; Corrêa, Márcio; Tonello, Paulo [UNESP] (Lepidus Tecnologia, 2021)
This article presents the theoretical foundations of the Capacitive Resistivity geophysical method, applied, more recently, in geological investigations and environmental diagnostics, with the objective of inserting it within the classification established for the geoelectric methods and which has served as a reference to the different technical texts and academic articles in recent years. Due to this inclusion, it was essential to carry out readjustments in the existing classification, as well as necessary changes to update it. From these changes, a new reclassification of geoelectric methods is proposed based on the fundamental structure already established, but more open to the possibilities of the emergence of new technologies and more appropriate to the geophysical methods applied to the investigation of underground contamination and that work with electrical resistivity or conductivity. In addition, in the course of the discussions presented, some synonyms are reported that have already been used in technical memorials or academic works, and which should be disclosed to the full knowledge of those who work in the area of Applied and Environmental Geophysics, as well as translations of some technical terms for the Portuguese language in the reclassification proposed here.
Método de resistividade capacitiva e reclassificação dos métodos geoelétricos para estudos hidrogeológicos e de contaminação subterrânea